Experiences of Self-Management Support Following a Stroke: A Meta-Review of Qualitative Systematic Reviews. - Gemma Pearce; Gemma Pearce; Hilary Pinnock; Eleni Epiphaniou; Hannah L Parke; Emily Heavey; Christopher J Griffiths; Trish Greenhalgh; Aziz Sheikh; Stephanie J C Taylor (PLoS ONE)
Background Supporting self-management in stroke patients improves psychological and functional outcomes but evidence on how to achieve this is sparse. We aimed to synthesise evidence from systematic reviews of qualitative studies in an overarching meta-review to inform the delivery and development of self-management support interventions. Methods We systematically searched eight electronic databases including MEDLINE, EMBASE and CINAHL for qualitative systematic reviews (published January 1993 to June 2012). We included studies exploring patients', carers' or health care professionals' experiences relevant to self-management support following a stroke, including studies describing the lived experience of surviving a stroke. We meta-synthesised the included review findings using a meta-ethnographic framework. Results Seven reviews, reporting 130 unique studies, were included. Themes emerging from the reviews were pertinent, consistent and showed data saturation; though explicit mention of self-management support was rare. Our meta-review highlighted the devastating impact of stroke on patients' self-image; the varying needs for self-management support across the trajectory of recovery; the need for psychological and emotional support throughout recovery particularly when physical recovery plateaus; the considerable information needs of patients and carers which also vary across the trajectory of recovery; the importance of good patient-professional communication; the potential benefits of goal-setting and action-planning; and the need for social support which might be met by groups for stroke survivors. Conclusions The observed data saturation suggests that, currently, no further qualitative research simply describing the lived experience of stroke is needed; we propose that it would be more useful to focus on qualitative research informing self-management support interventions and their implementation. Our findings demonstrate both the on-going importance of self-management support and the evolving priorities throughout the stages of recovery following a stroke. The challenge now is to ensure these findings inform routine practice and the development of interventions to support self-management amongst stroke survivors.